Relationship between the extent of implementation of the process management principles and the legal form of the business and business activity - Maříková, Monika; Rolinek, Ladislav; Kubecová, Jana; Vrchota, Jaroslav (Serbian Journal of Management, 2015)
Nowadays, enterprises are challenged with continuously changing environment and they have to react quickly to these changes. Process management can be a tool that greatly helps businesses in this difficult time to survive (Hora, 2010). Process Management brings a relatively new perspective on corporate governance. According to McCoy and Sinur (McCoy, Sinur, & Bill, 2007) enterprises which implemented rules of process management have a competitive advantage over others. The paper presents the application of the principles of process management in relation to the legal form of business enterprise and business activity. For determining the level of principles of process management was used indicator MPP (Rolínek, 2012; Truneček, 2005). Based on statistical analysis can be argued that there is a relationship between the application of the principles of process management, business legal forms and also business activities.